2016
DOI: 10.1155/2016/1248470
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Illness in Pregnant Indian Women: A Cross-Sectional Study

Abstract: Data about burden of influenza in pregnancy in India are scant. In order to assess the contribution of influenza to acute respiratory illness (ARI) in pregnancy, 266 north Indian pregnant females with febrile ARI were studied from December 2014 to May 2015. Twin nasopharyngeal/oropharyngeal swabs were obtained and tested for influenza viruses by RT-PCR. Fifty (18.8%) patients tested positive for influenza (A/H1N1pdm09 in 41, A/H3N2 in 8, and influenza B Yamagata in 1). Rigors, headache, and a family history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Another neglected disease in pregnancy is Influenza, though it has been associated with considerable morbidity and mortality [6]. Historically in the 1918 pandemic, it was seen that the overall mortality among pregnant females who developed influenza-associated pneumonia was 27% and it exceeded 50% in the third trimester of pregnancy [33].…”
Section: Influenza In Pregnancy-neglected But Importantmentioning
confidence: 99%
See 4 more Smart Citations
“…Another neglected disease in pregnancy is Influenza, though it has been associated with considerable morbidity and mortality [6]. Historically in the 1918 pandemic, it was seen that the overall mortality among pregnant females who developed influenza-associated pneumonia was 27% and it exceeded 50% in the third trimester of pregnancy [33].…”
Section: Influenza In Pregnancy-neglected But Importantmentioning
confidence: 99%
“…There are limited data describing the burden of influenza in pregnancy in India [6]. However, few sporadic studies can be found.…”
Section: Influenza In Pregnancy-neglected But Importantmentioning
confidence: 99%
See 3 more Smart Citations